Śrāvakadharmasopānam: a religious exercitation for disciples (śrāvkās) = Religious exercitation for disciples (śrāvkās) - Siṅghaī, Śrīyāṃśakumāra (Prācyavidyā evaṃ Jaina Saṃskr̥ti Saraṃkṣaṇa Saṃsthāna, 2023)
On Jaina ethics.